Studi Literatur: Analisis Media Pembelajaran Bahasa Indonesia Guna Meningkatkan Keterampilan Literasi Siswa SD - Eko Rahmad Juniawan; Haryadi Haryadi (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2022)
The purpose of this article is to discuss Indonesian language learning media used in elementary schools to help children develop reading skills. This is a literature review using content analysis techniques. To improve students' reading skills in elementary schools, researchers study relevant research from national, international journals, and other written works that are relevant to the topic of articles on Indonesian language learning media. Researchers go through several stages in reviewing previous research, including: 1) Sorting out relevant research; 2) Collecting data and information for review; 3) Determining the state of the art from research that has been analyzed; 4) Developing the results of information analysis and stringing them into a conclusion. The results of this study can be concluded that the existence of learning media is very important in improving reading skills, especially at the elementary school level. It is necessary to use Indonesian language learning media in order to achieve the learning objectives desired by the teacher Keywords: Learning Media, Indonesian Language, Reading Skills, Elementary School